Pengembangan Instrumen Penilaian Karakter Untuk Siswa Sekolah Dasar (SD) - Nisa, Khairun; Nurhasanah, Nurhasanah; Kusuma, Anindita Suliya Hangesti Mandra; Deni Sutisna, Deni Sutisna; Sari, Mega Puspita (Jurnal Ilmiah Profesi Pendidikan, 2021)
The issue of the character of the nation is still in the sharp spotlight by the community. The characters which at the same time include national culture cover various aspects of life. Even though it has long been echoed in every educational unit, character development seems to be the only writing that is always at the beginning of the lesson plan without any measurement tools.This research aims to explain the form of character assessment instruments developed for elementary school (SD) students. This type of research is development. The product produced from this development research is a character assessment instrument. The development design that will be used is the ADDIE instructional design. The results of internal validation of the instrument show that the questionnaire developed is very valid and can be used without improvement. External validation of the character assessment instrument for low classes, it is known that all statement items in the instrument are valid. The reliability of the low-class character assessment instrument was 0.986 in the first test and 0.984 in the second test. External validation of the character assessment instrument for high class, it is known that all statement items are valid. The reliability of the high-class character assessment instrument on the first test was 0.980 (very high) and on the second test was 0.979 (very high). Recommendations for development results are character assessment instruments that need to be tested in research on normal (offline) learning and still need to be evaluated (after being implemented) based on the input obtained from the response questionnaire or field notes on the observation sheet.